Chemical resistance of carbon, basalt, and glass fibers used in FRP reinforcing bars. (November 2019) - Cousin, P; Hassan, M; Vijay, PV; Robert, M; Benmokrane, B
One of the most important fields of research dealing with the use of carbon-, basalt-, and glass-fiber composites in the civil construction industry is their behavior under various chemical exposure conditions. Fiber-reinforced-polymer composites used as internal and external reinforcement in various structural applications can be subjected to widely differing pH situations. This study investigated the chemical durability of various carbon, basalt and glass fibers. The fibers were immersed in four types of solutions with acid, saline, alkaline, and deionized-water conditioning schemes. The fiber mass loss and surface damage along with changes due to chemical reactions were observed through weight-loss measurements and scanning electron microscopy. A criterion was developed to characterize the performance of fibers as very good, good, fair, and poor. This methodology can also be used by manufacturers as a quick quality-control tool for evaluating the chemical resistance of different fibers prior to large-volume production. The results reveal that the carbon fibers exhibited higher chemical resistance than the basalt and glass fibers based on weight loss and evidence of chemical reactions. Moreover, the determination of the fiber chemical composition before and after conditioning in acid and alkaline solutions clearly shows that the E-glass fibers, which are known to contain boron, were very sensitive to chemical corrosion. The ECR-glass fibers showed excellent chemical durability, even better than the basalt fibers.